2017
DOI: 10.1136/gutjnl-2017-313713
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of irritable bowel syndrome and chronic fatigue following GI infection: a population-level study using routinely collected claims data

Abstract: Psychological disorder and GI infections are distinct risk factors for IBS. The high incidence of non-specific GI infection suggests that postinfectious IBS is a common clinical occurrence in primary care. Chronic fatigue is a further significant sequela of GI infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 56 publications
2
50
1
2
Order By: Relevance
“…For example asthma and IBS might share an inflammatory aetiology but there are conflicting results concerning the effect of concurrent oral steroids IBS. 25,27,32 In conclusion, this review has shown that, in addition to gastroenteritis, there is a consistent and reasonably strong statistical association between onset of IBS and a range of pre-existing medical disorders (gastrointestinal and other), prior anxiety, depression, stress, frequent healthcare use and other pain disorders. 29 Several studies have shown that the psychological and general medical risk factors are independent and their affects are additive.…”
Section: Breadth and Strength Of Risk Factorsmentioning
confidence: 73%
See 1 more Smart Citation
“…For example asthma and IBS might share an inflammatory aetiology but there are conflicting results concerning the effect of concurrent oral steroids IBS. 25,27,32 In conclusion, this review has shown that, in addition to gastroenteritis, there is a consistent and reasonably strong statistical association between onset of IBS and a range of pre-existing medical disorders (gastrointestinal and other), prior anxiety, depression, stress, frequent healthcare use and other pain disorders. 29 Several studies have shown that the psychological and general medical risk factors are independent and their affects are additive.…”
Section: Breadth and Strength Of Risk Factorsmentioning
confidence: 73%
“…[25][26][27][28] Similarly chronic liver disease and fibromyalgia were independent and together they doubled the hazard ratio for IBS. [25][26][27][28] Similarly chronic liver disease and fibromyalgia were independent and together they doubled the hazard ratio for IBS.…”
Section: Risk Factors For New Onset Ibsmentioning
confidence: 94%
“…Female predominance in prevalence during the first 60‐70 years of life and a dissolution of this gender difference in people aged >65 years suggest an influence of gonadal sex hormones on IBS . Previous gastrointestinal infection has been shown to enhance the risk of IBS later on, but also other and non‐intestinal diseases . It is unclear whether the so‐called postinfectious IBS has to be considered as an own entity or whether the infection should be regarded as one risk factor among others .…”
Section: Introductionmentioning
confidence: 99%
“…The impulse for this paper and the hypothesis it promotes (biology first!) was provided by a recently published paper . It claimed that, of the 2.5 million Bavarian adults who had consulted a physician between 2005 and 2013, more than 500 000 cases of infectious enteritis were identified.…”
Section: A Pi‐ibs Cohort Studymentioning
confidence: 99%